Analisis Brand Switching dan Strategi Pemasaran Menggunakan Markov Chain dan Game Theory di Kota Medan - Rendy Ihsan Halim; Pardomuan Sitompul (Lembaga Pengembangan Kinerja Dosen, 2024)
This research analyzes the competitive strategies among Shopee, Lazada, and Tokopedia using Game Theory and Markov Chain, focusing on the marketing mix: price, promotion, security, service, and product availability. The results reveal varied optimal strategies. For instance, in the Shopee vs. Lazada competition, Shopee excels in price (0.66), security (0.124), and product availability (0.208). In the Shopee vs. Tokopedia competition, Shopee prioritizes price (0.129), security (0.375), and product availability (0.33315), while Tokopedia emphasizes price (0.5) and service (0.5). In the Lazada vs. Tokopedia scenario, Lazada stands out in security (0.5826) and product availability (0.4174), whereas Tokopedia focuses on price (0.749) and service (0.251). Regarding customer transition using the Markov Chain, the brand transition probabilities are Shopee (0.469), Lazada (0.306), and Tokopedia (0.223). In conclusion, optimal E-commerce strategies involve 5 different approaches, with variations depending on the competitive pair. The probability of customer transition can be measured through the Markov Chain approach.